KEHIDUPAN CORP TJADANGAN NASIONAL (CTN) DI BUKIT NILAM PASAMAN PADA MASA PRRI (1956-1958) (Universitas PGRI Sumatera Barat, 2013)
This study discusses the future life of CTN in Pasaman PRRI. CTN is specifically affected by the rationalization of past insurgent Hatta cabinet. CTN is a good Javanese who came from Yogyakarta, Java or people who have lived in Borneo. CTN to Pasaman particular arrival to Bukit Nilam, because villages Bukit Nilam is a former Dutch plantation on the emergence PRRI events sentiment against the Minang people of Java, especially in Bukit Nilam. Consequently CTN life suffered. The purpose of this study is: 1) to describe the early arrival of CTN in Bukit Nilam Pasaman?, 2) describing life in Bukit Nilam CTN Pasaman PRRI period (1958-1961).This research method historical method. At the start of data collection (heuristics), which is looking for documents, newspapers and books relating to the future life of CTN PRRI. Further interviews were conducted with members of CTN and people who witnessed the events in Pasaman PRRI. Once the data is collected is done critique sources, sifting through by category or research focus, then describe in writing (historiography)Results of the study can be concluded: 1) CTN in Pasaman a Javanese former army general who came from Borneo. CTN reason to Pasaman arrival because in Borneo is not possible to live a better life. CTN Pasaman placed in areas especially in Bukit Nilam, because Bukit Nilam is a former Dutch colonial era plantation. After the independence of Indonesia Nilam Bukit submitted by the Dutch royal Indonesian government, particularly the Minister of Defense and Security (Minister of Defense). CTN in Bukit Nilam is placed. 2) in the early 1956 arrival CTN life does not have problems, they live in peace with the people around Bukit Nilam. But in 1958 occurred PRRI events bring bad impact on the lives of CTN in Bukit Nilam Pasaman, tranquility and peace that we have enjoyed for two years now pepecahan that led to the expulsion, even the killing of members of CTN. CTN real Javanese and central government support so that they are experiencing life problems.